Adding rituximab to CODOX-M/IVAC chemotherapy in the treatment of HIV-associated Burkitt lymphoma is safe when used with concurrent combination antiretroviral therapy. (15th May 2015) - Alwan, Ferras; He, Annie; Montoto, Silvia; Kassam, Shireen; Mee, Matthew; Burns, Fiona; Edwards, Simon; Wilson, Andrew; Tenant-Flowers, Melinda; Marcus, Robert; Ardeshna, Kirit M.; Bower, Mark; et al.
<x xml:space="preserve">Abstract</x> Objectives: CODOX-M/IVAC (cyclophosphamide, vincristine, doxorubicin-methatrexate/ifusamide, etoposide, cytarabine) chemotherapy is commonly used to treat Burkitt lymphoma and in the HIV-negative population. Rituximab is often added with suggested survival benefits. Concerns over increased toxicity in an already immunocompromized population have prevented its routine addition in people living with HIV (PLWH). This study evaluated the effect on treatment-related toxicity and efficacy of adding rituximab to CODOX-M/IVAC chemotherapy in PLWH. Design: Retrospective review of 91 PLWH (74 men) with Burkitt lymphoma treated in five London centers between 2003 and 2013. All patients received combination antiretroviral therapy. Results: Forty-nine patients received CODOX-M/IVAC and 42 rituximab (R)-CODOX-M/R-IVAC. The addition of rituximab did not confer any significant increase in grade 3/4 toxicities including infections, mucositis, diarrhea, renal impairment, and tumor lysis syndrome. There was no significant difference in toxic deaths between groups (P = 0.14). The 2-year overall survival (OS) was greater for patients receiving rituximab 2-year OS 72% [95% confidence interval (CI) 0.22–0.92, hazard ratio 0.46] vs. 55% [95% CI 1.1–4.5, hazard ratio 2.2]; log-rank P = 0.04. Similarly, the 2-year progression-free survival (PFS) was greater in the rituximab cohort [2-year PFS 81% (95% CI 0.21–0.99, hazard ratio 0.46) vs. 55% (95% CI 1.0–4.8, hazard ratio 2.2); log-rank P = 0.04]. Conclusion: Our multicenter analysis is the largest to date in this population and showed that the addition of rituximab to CODOX-M/IVAC chemotherapy confers no increase in toxicity and results in significantly improved OS and PFS in PLWH with Burkitt lymphoma who receive concomitant combination antiretroviral therapy.